Managing Ibadan municipal secondary schools in periods of increasing national insecurity to educational institutions, Oyo State, Nigeria (2013)
The problem of insecurity to educational institution has attracted the attention of stakeholders in recent years hence this study investigated insecurity in Ibadan Municipal schools. Specifically, the study investigated the state of facilities in public and private secondary schools. The survey research design of the 'ex post facto' type was adopted that covered a population of principals, teachers and students. 3 Local Government Areas [LGA]s -Ibadan North, Ibadan Northeast and Egbeda LGAs were selected for the study using the Multi stage sampling procedure to select 56 schools with 112 principals and teachers at each level of selection. Three instruments namely Oyo State Secondary Schools Security Instrument Questionnaire (OSSSSIQ)l, 2 and 3 were adopted to elicit responses from respondents. The instrument was validated by colleagues in the Department of Educational Management of the Faculty of Education and test construction experts in the Institute of Education of the University of Ibadan. A reliability coefficient of ‘r=0.82’ was obtained in a trial test. 3 research questions and 3 hypotheses guided the study. Findings showed that a significant difference existed between the items (infrastructure, environment and personal) security in the 2 types of institutions (public and private) with [t(54)=3.123;p<0.05). Also, a significant difference could not be established between security awareness, insecurity avoidance and security defence between public and private secondary institutions in Oyo state with [t(76)=-0.835:p<0.05). Mean of Private schools stood at (m=1.43, sd = 0.480) while the same for public schools stood at (m=1.43 and sd=0.500). Finally the result established that r2 = 0.000. In essence, no proportion of the dependent variable can be explained by the independent variable which is not significant with r=0.97;p<0.05. It is recommended that more training should be carried out for teachers and students on security.